Pobreza, desigualdade e assistência social : um estudo dos programas de transferência de renda do México, Brasil, Colômbia e Chile - Damasceno, Luiz Rogério da Silva (2017)
The present dissertation sought to analyze social assistance as the predominant public policy of intervention in the issue of poverty in its different dimensions and conceptions, emphasizing for both its character of fundamental and human right, using as theoretical reference the conceptions of social justice of John Rawls and Amartya Sen, also addressing solidarity and inequality as related issues. Starting from a historical foreshortening around the reconstruction of the concept of poverty, the evolution of the assistance action destined to the needy was verified, which went through a primitive period in which the mendicancy was object of exclusion and punishment until arriving at the present moment, where Poverty is seen as the real social issue, the result of political choices and the prevailing social will, and, on account of that, deserves social protection. Finally, the direct transfer of financial resources to the poorest was analyzed with the main public assistance policy, based on conditional income transfer programs in four Latin American countries (Mexico, Brazil, Colombia and Chile).